Molecular mechanisms of ageing in cancer development and therapeutic response: Translational implications for precision oncology - Laiba Husain (Clinical and Translational Discovery, 2025)
Abstract Background The intricate relationship between cellular ageing processes and cancer development represents one of the most significant challenges in contemporary oncology. As populations worldwide experience unprecedented demographic shifts towards advanced age, understanding the molecular mechanisms that link ageing to cancer initiation, progression, and therapeutic response has become essential for developing effective precision medicine approaches. Main body This review examines the fundamental molecular pathways through which ageing influences cancer biology, including telomere dysfunction, cellular senescence, DNA damage accumulation, and epigenetic alterations. These age‐related changes create a permissive environment for oncogenesis while simultaneously affecting therapeutic efficacy and treatment tolerance. Key ageing‐associated molecular signatures include p16^INK4a^ upregulation, shortened telomeres, increased DNA damage response activation, and altered chromatin structure. The accumulation of senescent cells with age contributes to chronic inflammation and tissue dysfunction that promotes tumour development. Additionally, age‐related changes in drug metabolism, DNA repair capacity, and immune function significantly impact therapeutic outcomes. Recent advances in molecular ageing biomarkers, including transcriptomic ageing clocks and protein‐based signatures, offer promising approaches for personalizing cancer treatment strategies. The integration of ageing biology into precision oncology frameworks presents opportunities for developing age‐informed therapeutic protocols that optimize efficacy while minimizing toxicity. Emerging technologies, including artificial intelligence‐driven molecular analysis and advanced imaging techniques, enable more precise characterization of ageing‐cancer interactions at the cellular and tissue levels. Conclusion The molecular mechanisms underlying ageing‐cancer relationships provide critical insights for advancing precision oncology approaches. Understanding these pathways enables the development of targeted interventions that account for age‐related biological changes, ultimately improving therapeutic outcomes for older cancer patients. Future research must focus on translating molecular ageing discoveries into clinically actionable tools that enhance treatment personalization and optimize care delivery across the cancer continuum.